Haemospermia due to Dengue fever – Case report of an atypical presentation of dengue (Bangladesh Journal of Urology, 2025)
Dengue is a mosquito borne viral disease common in regions with tropical climates. To date, it is estimated that >55% of the population worldwide is exposed to dengue virus (DENV), an RNA virus from the genus Flavi virus of the Flaviviridae family. Most dengue-infected persons are asymptomatic or develop a mild form of the disease with common signs and symptoms resembling those of influenza, such as fever, retroocular pain, headache, rash, muscle and joint pain, nausea, vomiting, and fatigue. However, a small proportion of infections progress to severe illness that can cause rapid onset of capillary leakage leading to bleeding, thrombocytopenia, and rapid shock. Dengue Haemorrhagic Fever (DHF) has diverse manifestations ranging from petechial skin haemorrhages to life threatening gum , gastrointestinal ,cerebral, pulmonary haemorrhag  and haematuria. However, haemospermia with DHF is not well documented in literature. We report a rare case of haemospermia  due to Dengue.Bangladesh J. Urol. 2024; 27(1): 84-86